2000
DOI: 10.1177/002215540004800504
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Peroxisome Proliferator-activated Receptors (PPARs) in the Developing Human Fetal Digestive Tract

Abstract: SUMMARY We investigated the spatiotemporal distributions of the different peroxisome proliferator-activated receptor (PPAR) isotypes (α, β, and α) during development (Week 7 to Week 22 of gestation) of the human fetal digestive tract by immunohistochemistry using specific polyclonal antibodies. The PPAR subtypes, including PPARα, are expressed as early as 7 weeks of development in cell types of endodermal and mesodermal origin. The presence of PPARα was also found by Western blotting and nuclease-S1 protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 49 publications
3
73
0
Order By: Relevance
“…Peroxisome proliferator-activated receptor (PPAR) g is a ligand-dependent transcription factor belonging to the nuclear receptor superfamily (16); it is highly expressed in adipose tissue, where it plays a key role in the regulation of adipocyte differentiation and fat metabolism (17,18), and in colonic mucosa, where it exerts important functions in the differentiation process (19,20). It is a functional receptor for the thiazolidinedione (TZDs) class of antidiabetic drugs and may function as a tumor-suppressor gene (21,22); its activation has been reported to induce differentiation of liposarcoma (23), prostate cancer (24) or several transformed cells (19,25).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor (PPAR) g is a ligand-dependent transcription factor belonging to the nuclear receptor superfamily (16); it is highly expressed in adipose tissue, where it plays a key role in the regulation of adipocyte differentiation and fat metabolism (17,18), and in colonic mucosa, where it exerts important functions in the differentiation process (19,20). It is a functional receptor for the thiazolidinedione (TZDs) class of antidiabetic drugs and may function as a tumor-suppressor gene (21,22); its activation has been reported to induce differentiation of liposarcoma (23), prostate cancer (24) or several transformed cells (19,25).…”
Section: Introductionmentioning
confidence: 99%
“…12 PPARs are expressed in the intestine at various levels. [13][14][15] Recently, it has been also demonstrated that PPAR-a is also expressed in the digestive tract mainly localized in the intestinal mucosa in the small intestine and in the colon. [13][14][15] In particular, it has been demonstrated that there is a higher expression of PPAR in the more differentiated colonic epithelial cells facing the intestinal lumen as compared to cells in the lower parts of the crypts.…”
mentioning
confidence: 99%
“…[13][14][15] Recently, it has been also demonstrated that PPAR-a is also expressed in the digestive tract mainly localized in the intestinal mucosa in the small intestine and in the colon. [13][14][15] In particular, it has been demonstrated that there is a higher expression of PPAR in the more differentiated colonic epithelial cells facing the intestinal lumen as compared to cells in the lower parts of the crypts. 13 PPAR-a binds to a diverse set of ligands, namely, arachidonic acid metabolites (prostaglandins and leukotrienes) and plasticizers and synthetic fibrate drugs including clofibrate, fenofibrate and bezafibrate.…”
mentioning
confidence: 99%
“…PPARa is expressed mainly in brown adipose and liver, but is also expressed in the intestine (14,15). The biology of PPARa in the intestine remains poorly defined, although lipid metabolism in the intestine profoundly affects systemic energy homeostasis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…One of them, PPARa, is highly expressed by brown adipose tissue, liver, kidney, heart, and skeletal muscle. Emerging evidence indicates that PPARa is also expressed in the digestive tract and engages in several physiological events such as intestinal permeability and immune response (14)(15)(16)(17). However, no evidence related to the exact biological role of PPARa exists in the intestinal lipid metabolism.…”
mentioning
confidence: 99%